2007
DOI: 10.1080/00207540600690511
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise resource planning (ERP) systems and the manufacturing–marketing interface: an information-processing theory view

Abstract: This is an electronic version of an article published in Gattiker, TF. (2007). ERP Systems and the manufacturing-marketing interface: An information processing theory view. International Journal of Production Research, 45(13): 2895-2917.. International Journal of Production Research is available online at: http://www.informaworld.com/smpp. DOI: 10.1080/00207540600690511This is an electronic version of an article published in Gattiker, TF. (2007). ERP Systems and the manufacturing-marketing interface: An inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…For instance, Flynn and Flynn (1999) examined a variety of information processing approaches in the manufacturing context and found environmental uncertainty to negatively influence organizational performance, whereas IT investments had no significant influence. In an ERP context, Gattiker (2007) found interdependence among the firm's subunits to be a source of uncertainty, this author stating that "the greater the interdependence between marketing and operations the greater the benefit of a highly integrative coordination mechanism such as ERP" (p. 2911). More recently Cegielski et al (2012) used information processing theory to assess how a firm's information processing requirements and capabilities combine to affect the intention to adopt cloud computing as an enabler of supply chain management systems.…”
Section: Information Processing Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Flynn and Flynn (1999) examined a variety of information processing approaches in the manufacturing context and found environmental uncertainty to negatively influence organizational performance, whereas IT investments had no significant influence. In an ERP context, Gattiker (2007) found interdependence among the firm's subunits to be a source of uncertainty, this author stating that "the greater the interdependence between marketing and operations the greater the benefit of a highly integrative coordination mechanism such as ERP" (p. 2911). More recently Cegielski et al (2012) used information processing theory to assess how a firm's information processing requirements and capabilities combine to affect the intention to adopt cloud computing as an enabler of supply chain management systems.…”
Section: Information Processing Theorymentioning
confidence: 99%
“…In this research, we define information processing capability as an organization's capacity to utilize and structure information in a meaningful fashion that supports decision making (Tushman and Nadler, 1978). Previous research suggests that IT is a key aspect of an organization's information processing capability (Cegielski et al, 2013;Melville and Ramirez, 2008;Gattiker, 2007;Premkumar et al, 2005). Tushman and Nadler (1978) assert that, within organizations, formalized information systems, and particularly ones that are IT-based, are the most complex but provide the highest capacity for organizational information processing.…”
Section: Information Processing Capacitymentioning
confidence: 99%
“…However our study found only a moderate support for this notion. Similarly enterprise-wide computer systems (ERP) are also commonly accepted as a tool to achieve enterprise-wide integration (Gattiker, 2007;Davenport, 2000). Our study however, did not find any significant effect of ERP systems on internal supply chain integration.…”
Section: Strmentioning
confidence: 99%
“…From one perspective, supply chain IT has the capability, along with enterprise resource planning systems (Gattiker 2007), to bridge functional silos existent among marketing, production, and distribution. From another perspective, long-term buyer-seller relationships (e.g., Dwyer et al 1987;Morgan and Hunt 1994) are strongly facilitated by supply chain IT.…”
Section: Discussionmentioning
confidence: 99%